Titanium Nitride Sensing Film-Based Extended-Gate Field-Effect Transistor for Chemical/Biochemical Sensing Applications. Issue 10 (27th October 2021) - Kumar, Dhirendra; Jit, Satyabrata; Sinha, Soumendu; Sharma, Rishi; Mukhiya, Ravindra
Abstract : Extended-Gate Field-Effect Transistor (EGFET)-based pH sensors are cost-effective alternatives to well-established Ion-Sensitive Field-Effect Transistor (ISFET) technology for chemical/biochemical sensing applications. In this work, a ∼70 nm thin sensing film of Titanium Nitride (TiN) was deposited on Indium-Tin Oxide (ITO)-coated glass substrate using a pulsed-DC magnetron-assisted reactive sputtering technique to fabricate EGFET electrode. TiN-EGFET sensor electrode was electrically connected to the gate terminal of a commercial MOSFET (MC14007UBCP) to constitute an EGFET pH sensing platform, which was tested using pH buffer solutions of pH range 2–12 (at 35 °C) and its sensitivity was found to be ∼61 mV/pH. TiN-EGFET devices have a fast and linear response in the pH range 2–12. Drift analysis of the sensor was also performed for 10 min in each pH buffer solution of pH = 2, 4, 7, 10, 12; where a low-drift of about 0.5 μ A min −1 has been obtained for the pH range of 2–10 and a hysteresis response of nearly 10 μ A has been obtained for pH cycle 7 → 10 → 7 → 4 → 7. The repeatability of the sensor was studied for seven days, where a stable response was recorded in each of the pH buffer solutions, which confirms the repeatability and reliability of the TiN-EGFET sensor.